Pendampingan Pengenalan Metode Bermain Peran dalam Mengembangkan Kemampuan Bahasa Anak Usia Dini di TKA/DTA/TPA Bustanul Ulum - Sari, Dita Kumala (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
The purpose of this mentoring activity is to introduce the role-playing method in developing language skills in early childhood which is useful as their vocabulary to be able to communicate with others. The mentoring implementation time is July 10, 2024. This service is carried out with a counseling and training approach. The results of community service activities, that the aspects that can be produced from applying the role-playing method in developing language skills are (1) children are able to string together words from a sound (phoneme), (2) children are able to recognize new vocabulary (morphology), (3) children are able to arrange words into a sentence (syntax), (4) children are able to use sentences according to purpose (semantics). In order for children's language skills to continue to develop, teachers and parents must often train children's language skills with various methods, one of which is the role-playing method so that children get more vocabulary to communicate